Seed amplification assay results illustrate discrepancy in Parkinson’s disease clinical diagnostic accuracy and error rates - Middleton, John Stephen; Hovren, Hanna Lynn; Kha, Nelson; Medina, Manuel Joseph; MacLeod, Karen Ruth; Concha-Marambio, Luis; Jensen, Kendal Jay (Journal of neurology, 2023)
Parkinson’s disease (PD) may be misdiagnosed due to the clinical overlap between PD and atypical parkinsonism. The utility of α-Synuclein (αSyn) Seed Amplification Assay (SAA) as a diagnostic indicator for PD has been reported in numerous studies, but never when administered as a validated clinical laboratory test. This study compares results from αSyn-SAA validation testing performed using well-characterized cohorts from two biorepositories to better understand the accuracy of PD clinical diagnosis. Blinded cerebrospinal fluid (CSF) specimens from a repository that included cohorts of subjects clinically diagnosed as PD or healthy controls, both with confirmatory dopamine transporter single-photon emission computed tomography (DAT SPECT) imaging, and blinded CSF specimens from a repository that included cohorts of subjects clinically diagnosed as PD or healthy controls based on clinical diagnosis alone, were tested as part of the validation studies for the diagnostic αSyn-SAA test (SYNTap® Biomarker Test). Measured αSyn-SAA test accuracy was 83.9% using clinical diagnosis as comparator, and 93.6% using clinical diagnosis with confirmatory DAT- SPECT imaging as comparator. The statistically significant discordance between accuracy determinations using specimens classified using different diagnostic inclusion criteria indicates that there is some symbiosis between dopamine-weighted imaging and αSyn-SAA results, both of which are associated with higher accuracy compared with the clinical diagnosis alone.